Changes in Cigarette Smoking Behavior in Cancer Survivors During Diagnosis and Treatment. Issue 10 (21st March 2022) - Jose, Thulasee; Schroeder, Darrell R; Warner, David O
Abstract: Introduction: Continued cigarette smoking is a critical determinant of outcome in oncology patients, but how the separate events of cancer diagnosis, cancer treatment, and completion of treatment affect smoking behavior in cancer survivors is unknown. This study described such changes, hypothesizing that they would be more pronounced for smoking-related cancers. Methods: The Cancer Patient Tobacco Use Questionnaire (CTUQ) was sent to every cancer patient ≥ 18 y old scheduled for outpatient visits at the Mayo Clinic Cancer Center with a current or former history of tobacco use. Results: From September 2019 to September 2020, 33, 831 patients received the CTUQ, and 20, 818 (62%) responded. Of the 3007 current smokers analyzed, 34% quit at diagnosis; those with smoking-related cancers were more likely to quit (40% vs. 29%, respectively, p < .001). Among those who did not quit at diagnosis, 31% quit after starting cancer treatment, and those with smoking-related cancers were more likely to quit (35% and 28%, respectively, p = .002) Among those who had quit before the completion of treatment, 13% resumed smoking after treatment ended. In multivariable analysis, patients with smoking-related cancers were more likely to report 30-d point prevalence abstinence from pre-diagnosis to the completion of treatment (adjusted OR 1.98 [95% CI 1.65, 2.36], p < .001). Conclusions: Both cancer diagnosis and treatment prompt smoking abstinence, with most maintaining abstinence after treatment is completed. Those with smoking-related cancers are more likely to quit. These results emphasize the need to provide access to tobacco treatment services that can further support cancer patients who smoke. Implications: Approximately one-third of cancer patients who smoke quit smoking at the time of diagnosis, an additional one-third of patients who had not yet quit did so at the initiation of treatment, and most sustained this abstinence after treatment completion. Patients with smoking-related cancers are more likely to quit. Thus, there are multiple opportunities within the cancer care continuum to intervene and support quit attempts or continued abstinence.